(untitled) (Jurnal Riset Agribisnis dan Peternakan, 2022)
The objective was to determine the effect of substitution of palm sugar and coconut sugar on the sensory quality of jerky meat of rejected laying hens. The design used was a completely randomized design (CRD). The treatments given were A0K30, A10K20, A20K10, A30K0. Parameters observed were taste, color, texture and aroma. The results showed that the substitution of palm sugar and coconut sugar affected aroma quality and hedonic aroma. The results of the ANOVA analysis showed that the substitution of palm sugar and coconut sugar was significantly different on the quality of the jerky aroma of rejected layers and the hedonic aroma of rejected layers of jerky. The quality score of the jerky aroma of rejected laying hens was significantly different (P<0.05). The hedonic score of the aroma of jerky laying hens was significantly different (P<0.05). The conclusion is that the substitution of palm sugar and coconut sugar in the sensory test is not significantly different except for aroma quality and hedonic aroma which affects jerky significantly.